TINJAUAN MENGENAI PERAN DAN FUNGSI DPR DALAM UUD NKRI TAHUN 1945 PASCA AMANDEMEN BERDASARKAN MEKANISME CHECK AND BALANCE - Yokotani, Yokotani (Fakultas Hukum Universitas Bangka Belitung, 2016)
Reforms in Indonesia has led to many changes, one change in the state administration system in Indonesia. Post authoritarian era, hopes to form a power ideally through the constitution amendment to be the only way to improve the existing system by step abolish one by one to the authority of the executive power into shades executive heavy, in order to power the institution country to be more balanced with a pattern of horizontal separation between state institutions